An Integrated Prognostic Classifier for Stage I Lung Adenocarcinoma Based on mRNA, microRNA, and DNA Methylation Biomarkers. Issue 7 (July 2015) - Robles, Ana I.; Arai, Eri; Mathé, Ewy A.; Okayama, Hirokazu; Schetter, Aaron J.; Brown, Derek; Petersen, David; Bowman, Elise D.; Noro, Rintaro; Welsh, Judith A.; Edelman, Daniel C.; Stevenson, Holly S.; et al.
Abstract : Introduction: Up to 30% stage I lung cancer patients suffer recurrence within 5 years of curative surgery. We sought to improve existing protein-coding gene and microRNA expression prognostic classifiers by incorporating epigenetic biomarkers. Methods: Genome-wide screening of DNA methylation and pyrosequencing analysis of HOXA9 promoter methylation were performed in two independently collected cohorts of stage I lung adenocarcinoma. The prognostic value of HOXA9 promoter methylation alone and in combination with mRNA and miRNA biomarkers was assessed by Cox regression and Kaplan–Meier survival analysis in both cohorts. Results: Promoters of genes marked by polycomb in embryonic stem cells were methylated de novo in tumors and identified patients with poor prognosis. The HOXA9 locus was methylated de novo in stage I tumors ( p < 0.0005). High HOXA9 promoter methylation was associated with worse cancer-specific survival (hazard ratio [HR], 2.6; p = 0.02) and recurrence-free survival (HR, 3.0; p = 0.01), and identified high-risk patients in stratified analysis of stages IA and IB. Four protein-coding gene (XPO1, BRCA1, HIF1α, and DLC1), miR-21 expression, and HOXA9 promoter methylation were each independently associated with outcome (HR, 2.8; p = 0.002; HR, 2.3; p = 0.01; and HR, 2.4; p = 0.005, respectively), and when combined, identified high-risk, therapy naive, stage I patients (HR, 10.2; p = 3 × 10 −5 ). All associations were confirmed in two independently collected cohorts. Conclusion: A prognostic classifier comprising three types of genomic and epigenomic data may help guide the postoperative management of stage I lung cancer patients at high risk of recurrence.